Swallowing Measurement for a Healthy Subject Using a Hetero-Core Optical Fiber Sensor - Koyama, Yuya; Nishiyama, Michiko; Aoki, Ryoko; Higashimori, Yuka; Watanabe, Kazuhiro (2019 IEEE 8th Global Conference on Consumer Electronics (GCCE), 2019)
Prevention of decreasing swallowing function is an important issue in quality of life, especially for late-stage elderly. To diagnose the decreasing function in a daily living environment, the measurement system needs to be compact and straightforward for uses and non-invasive for the human body. In this paper, a swallowing measurement was described using medical film tape based on hetero-core fiber optics. The tape sensor placed on the thyroid cartilage can detect the motion non-invasively for users. The optical loss was compared with EMG sensor signals for reference. As a result, the swallowing movements were successfully measured using the tape sensor.